High Performance Liquid Chromatography Method to Detect Tramadol and Sildenafil in the Blood of Rats on Combination Treatment. - Fathy, Wael Mohamed; S. Farag, Rabie; El Nawawy, Mohamed; Atiaa, Hamada; Mahdy, Tarek (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Tramadol is one of widest abusedstreet drug inEgypt. Recently, drug abusers were taking tramadol beside sildenafil for sexual purposes.So it was important to develop a newHPLC method for the simaultineous determination of tramadol andSildenafil in the blood of rats exposed to a combination of specific dose of tramadol and sildenafil. Sample preparation involved liquid–liquid extraction with methyl tertiary butyl ether (MTBE) and backextraction with hydrochloric acid.Tramadol,sildenafiland the internalstandardnalbuphine were separated by reversed phaseHPLCusing60%acetonitrileand 40% 20mMsodium phosphate bufferpH 7.5. Detection was by using UV at wavelengths 230 nm. The method was linear fortramadol (0.8–100ug/ml) and Sildenafil (0.3–100 ug/ml) with mean recoveries of 97.2% and 100.8%, respectively. Intra- and inter-day precisionswere 9.34% and 9.12% for tramadol and 11.82%, and10.43% for sildenafilat the respective limits of quantitation (0.8 and 0.3ug/ml). Accuracy fortramadol and Sildenafil ranged from 96.6% to 97.8%and 99.2% to 101.3% respectively. The method was applied to apharmacokinetic study of tramadol and sildenafil in rats.